Sistem Informasi Penggajian Berbasis Web Dengan FiturSms Gateway (Studi Kasus : Smp N 1 Pulokulon) - Probowati, Fitria Dewi; , Dr. Heru Supriyono, M.Sc (2016)
Calculation of salary is a very important sector in the institute. In SMP N 1 Pulokulon the payroll system is still using a conventional method that use a bookkeeping. It makes many errors in calculating the amount of salaries, because the data is too much that caused disadvantages to many parties. To support the importance of salary especially for Institute and employees, SMP N 1 Pulokulon need a system that useful for processing data to be more effective to allocate teacher salaries. This research aims to design and make a payroll information system that can be processed using a computerized system, and can provide information about salaries to teachers and employees. The system is equipped with SMS gateway which will provide information about the pieces of what will be left to the teachers and employees. Web-based payroll information system with SMS gateway feature is designed to use the PHP programming language and stored in a MySQL database. SMS gateway made by using Gammu as its service. The results of this analysis, is a WEB designed for treasurer as admin that useful for processing data to be sufficiently of large salary and SMS gateway feature to inform a salary cut imposed on teachers and employees. Based on the result of questioner, it shows that 83% of 20 respondent said that the system made by the researcher is very useful. Keyword : Information system, Payroll, SMS getway